Propuesta de mobiliario en espacio público en el municipio de Palmira Valle ¨Estudio caso parque La Emilia y parque Bolivar - Montaño Espinosa, Johan Fernando (Universidad Antonio Nariño, 2022)
This work seeks to investigate the problems that are evidenced by the poor design of the furniture in two points of the municipality of Palmira, appreciating its deterioration in ergonomic complexities and finally seeing its deterioration due to the lack and implementation of a materiality study. Based on the urban analysis and the furniture, models or prototypes of furniture are proposed in accordance with or that respond to the conditions of the place, applying materiality, ergonomics and aesthetics.